A Rereading of the Elderly Spatial Perception through Comparing Space Syntax and Cognition Maps; The Case of Kahrizak Elderly Home - Farnaz Cheraghi Far; Hossein Soltan Zadeh; Hadi Ghodousi Far (صفه)
As the age increases, the power and ability of the elderly to recognise architectural spaces and related internal or external areas decreases. This initially increases their dependence on others, and in the next stages they may lose the ability to find their way. The purpose of this research is to provide an understanding of the elements that play a role in the mental dimensions of aging. The present article was formed in order to answer these questions: ‘how does the perception and cognition of the elderly take place with a focus on environmental and human approaches’, and ‘what are the influential indicators in the perception and cognition of the elderly’. For this purpose, Kahrizak elderly home was chosen. Using the 'Space Syntax’ method, this article examines the behavioural and cognitive responses of the elderly regarding the spatial characteristics of the elderly home. The research method includes two cognitive and spatial parts. In the cognitive section, after interviewing the elderly and receiving cognitive maps, the findings from the cognitive maps were compiled. Space configuration was evaluated through depth map software and Space Syntax parameters. In this analysis, spatial parameters such as connection value, connectivity, selection, depth of access and resolution have been examined and compared with cognitive maps. The analyses show that the maximum correlation is 7.3 and its average is 3.5, the maximum and average correlation parameters are 20 and 8.6, respectively. The maximum and average selection parameters are equal to 67 and 11.06, respectively. The maximum and average access depth parameters are 257 and 138.7, respectively. The analysis shows that Space Syntax modelling can be effective for understanding the perceptibility of space by the elderly, but for a correct understanding of the same space, other methods such as cognitive maps are needed. The results show that multiple objective and subjective factors are effective in the elderly's perception and their knowledge of space, together and sometimes with priorities over each other.